Case-control study of infections with Salmonella enteritidis phage type 4 in England. Issue 6702 (23rd September 1989) - Cowden, J. M.; Lynch, D.; Joseph, C. A.; O'Mahony, M.; Mawer, S. L.; Rowe, B.; Bartlett, C. L.
Abstract : OBJECTIVE–To determine the source of indigenous sporadic infection with Salmonella enteritidis phage type 4. DESIGN–Case-control study of primary sporadic cases identified by the Public Health Laboratory Service between 1 August and 30 September 1988. SETTING–PHLS Communicable Disease Surveillance Centre, Division of Enteric Pathogens, 11 PHLS laboratories, and 42 local authority environmental health departments in England. SUBJECTS–232 Patients (cases) with confirmed primary sporadic infection, for 160 of whom (88 female) (median age 30 years, age range 4 months to 85 years) data were obtained by questionnaire about consumption of fresh eggs, egg products, precooked chicken, and minced meat in the three days and one week before onset of the symptoms. Up to three controls, matched for neighbourhood, age, and sex (if aged greater than 11 years), were asked the same questions for the same calendar period. MAIN OUTCOME MEASURE–Association of primary sporadic infection with consumption of suspected food items. RESULTS–Illness due to S enteritidis phage type 4 was significantly associated with consumption of raw shell egg products (homemade mayonnaise, ice cream, and milk drinks containing eggs) (matched p = 0.02) and shop bought sandwiches containing mayonnaise (matched p = 0.00004) or eggs (matched p = 0.02). Illness was also significantly associated with eating lightly cooked eggs (unmatched p = 0.02), but not soft boiled eggs, and precooked hot chicken (matched p = 0.006). Reported consumption of eggs was not appreciably different between cases and controls before or after the median date of interview. CONCLUSIONS–Fresh shell eggs, egg products, and precooked hot chicken are vehicles of S enteritidis phage type 4 infection in indigenous sporadic cases. Public health education and reduction in contamination of eggs and infection of poultry with S enteritidis are needed to reduce the incidence of human infection.